Measurement of the shape of the boson rapidity distribution for pp̄→Z/γ*→e+e-+X events produced at s of 1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2007)
We present a measurement of the shape of the boson rapidity distribution for pp̄→Z/γ*→e+e-+X events at a center-of-mass energy of 1.96 TeV. The measurement is made for events with electron-positron mass 71<Mee<111GeV and uses 0.4fb-1 of data collected at the Fermilab Tevatron collider with the D0 detector. This measurement significantly reduces the uncertainties on the rapidity distribution in the forward region compared with previous measurements. Predictions of next-to-next-to-leading order (NNLO) QCD are found to agree well with the data over the full rapidity range. © 2007 The American Physical Society.